(2x-1)(4x+6)=0

Simple and best practice solution for (2x-1)(4x+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(4x+6)=0 equation:



(2x-1)(4x+6)=0
We multiply parentheses ..
(+8x^2+12x-4x-6)=0
We get rid of parentheses
8x^2+12x-4x-6=0
We add all the numbers together, and all the variables
8x^2+8x-6=0
a = 8; b = 8; c = -6;
Δ = b2-4ac
Δ = 82-4·8·(-6)
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(8)-16}{2*8}=\frac{-24}{16} =-1+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(8)+16}{2*8}=\frac{8}{16} =1/2 $

See similar equations:

| 141=3(5x-3 | | 12-12y+y^2=0 | | 4-8y+y^2=0 | | 2x=−46 | | 120=6(5+3n) | | 12⋅(x+10)=10 | | 3x−2=28 | | 5x−18=17 | | |x+2|=-4 | | 4=x*2 | | 4-12y+y^2=0 | | -5(7+9x)=-125 | | 2x−1=19 | | 4x−13=3 | | -19=5n+2-8n | | 10+9n+5=-21 | | s-3/4=s-1 | | 16=6-9n+1 | | 2q-1÷3=3q | | 7x−11=10 | | X²-5x=14 | | 5x2-20x+20=0 | | (3x-4)/x+1=-3/1 | | -71=-31+2x | | a+2/4+a-3/5=3a-5/8 | | Y-y-5/2=1-2y | | x+7=17/6-5x/5 | | 0.1x²+0.2x+0.3=0.8x | | x^2+31x-360=0 | | (13/4)x^2+15x=200 | | 3(2x–8)=6 | | 3(2x–8)=6(4–3x) |

Equations solver categories